Antioxidant activity of formulation of Roselle calyx herbal syrup as a functional beverage - Kartini, Kartini; Dewi, Tan Angela Puspita; Wulandari, Septia Monica (Pharmaciana, 2025)
Roselle (Hibiscus sabdariffa) flowers are rich in anthocyanins and organic acids, which contribute to their characteristic red-colored calyx and sour flavor, along with notable biological activities. This study aimed to develop and optimize a functional roselle syrup formulation by incorporating selected spices—cinnamon, cloves, and cardamom—and using xanthan gum and Tween 60 as stabilizing agents. Six formulations (F1–F6) were prepared and evaluated based on their physicochemical characteristics, antioxidant activity, and stability. Among the formulations, F3 (containing 1% xanthan gum and 0.2% Tween 60) showed the most favorable results, with a pH of 2.73, viscosity of 403.3 cP, total anthocyanin content of 67.85 mg/L, and DPPH free radical inhibition of 50.43% and 64.05% at concentrations of 1% v/v and 2% v/v, respectively. Upon reconstitution at a 1:5 ratio, the syrup retained appealing organoleptic qualities, including a bright red color, sweet-sour taste, and herbal aroma. During a 42-day storage study, the syrup maintained stable viscosity and antioxidant activity for up to 21 days, with pH remaining within the acceptable range (2–4) despite a slight increase. However, anthocyanin content showed significant degradation after day 7. These findings highlight the need for further formulation improvement to enhance anthocyanin and antioxidant stability in roselle syrup products.